Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Keramik Viola Kota Probolinggo - Seger Priantono (Ecobuss, 2022)
This study was conducted with the aim of determining the influence of product quality and price simultaneously and partially on the purchasing decision of Viola ceramics in Probolinggo City; and to find out the variables between product quality and price that have a dominant influence on the purchasing decision of Viola ceramics in Probolinggo City. The type of research used is a correlational type of research, with the variables used consisting of product quality (X1), price (X2) and purchase decision (Y). The sample used was 62 consumers. The analysis method uses a quantitative descriptive method with statistics in the form of multiple regression analysis previously tested for the validity and adequacy of the data with tests of validity, reliability and classical assumption tests. The results showed that there was an influence between product quality and price simultaneously on the purchasing decision of Viola ceramics in Probolinggo City with a calculated value of F = 87.632 and a value of Sig. F = 0.00. The effect of variabal product quality partially on the purchase decision of Viola ceramics in Probolinggo City with a calculated value = 8.056 and a value of Sig. t = 0.000. The effect between the price partially on the purchasing decision of Viola ceramics in Probolinggo City with a calculated value = 2.589 and a value of Sig. t = 0.009. Product quality variables that have a dominant influence on the purchasing decision of Viola ceramics in Probolinggo City.